2007
DOI: 10.1108/00070700710761518
|View full text |Cite
|
Sign up to set email alerts
|

Observed food safety behaviours of young adults

Abstract: PurposeThe purpose of this paper is to observe young adults preparing two recipes in a controlled laboratory setting to identify food‐handling errors. Few studies have investigated actual consumer food safety and food‐handling practices.Design/methodology/approachThe paper shows that one of four trained observers used a check‐list to directly observe and record food‐handling practices; observation data were later analyzed to assess how closely participants followed recommended practices. The observation check‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 20 publications
6
58
0
1
Order By: Relevance
“…This implies the development of intentions to adopt food safety behaviours depends, partially, on expectations of parents, friends, media or health experts and the motivation to comply with these people. This complements the finding that food safety behaviour is usually taught by parents (Byrd-Bredbenner et al, 2007). Therefore the expectations of these people of importance should also be considered when encouraging individuals to develop intention to adopt food safety behaviours.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…This implies the development of intentions to adopt food safety behaviours depends, partially, on expectations of parents, friends, media or health experts and the motivation to comply with these people. This complements the finding that food safety behaviour is usually taught by parents (Byrd-Bredbenner et al, 2007). Therefore the expectations of these people of importance should also be considered when encouraging individuals to develop intention to adopt food safety behaviours.…”
Section: Discussionmentioning
confidence: 53%
“…Discrepancies between people"s knowledge of food safety behaviours and implementation of this information had been documented (Byrd-Bredbenner, Maurer, Wheatley, Cottone, & Clancy, 2007;Clayton, Griffith, & Price, 2003;Jay, Comar, & Govenlock, 1999a), with males in their late teens and early twenties being most at risk of causing food contamination. This demographic appears to be most susceptible to causing food poisoning because they are less concerned about food safety than other populations (Knight & Warland, 2004).…”
Section: Originality/valuementioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found consistent results among various age groups studied (i.e., young, elderly, employees, caregivers) and in different context areas (i.e., school, home, and workplace). While food safety training has been shown to increase food safety knowledge and attitudes (Wei & Strohbehn, 1997); having food safety training, knowledge, and a willingness to follow safe practices does not necessarily equate to safe food handling behaviors (Almanza, Namkung, Ismail, & Nelson, 2007;Byrd-Bredbenner, Maurer, Wheatley, Cottone, & Clancy, 2007;Dharod, Peréz-Escamilla, Bermúdez-Millán, Segura-Peréz, & Damio, 2004;Sneed & Henroid, 2007).…”
Section: Review Of Literaturementioning
confidence: 99%
“…An observation study carried out on undergraduate university students found that participants performed less than 50% of the food safety behaviours recommended to prevent foodborne illness (Byrd-Bredbenner et al, 2007). Approximately 20% of the Australian population are in enrolled in tertiary education, and approximately 60% of school leavers go on to some form of higher education (Australian Bureau of Statistics, 2009).…”
mentioning
confidence: 99%